Aspects of Twentieth Century Art. (London : Marlborough Fine Art Ltd., 1963)
Baumeister, Willi ; Bazaine, Jean ; Beaudin, André ; Beckmann, Max ; Brancusi, Constantin ; Braque, Georges ; Burri, Alberto ; Chagall, Marc ; Delaunay, Robert ; Dufy, Raoul ; Ernst, Max ; Estève, Maurice ; Gabo, Naum ; Giacometti, Alberto ; Gleizes, Albert ; Goncharova, Nathalia ; Gris, Juan ; Hartung, Hans ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Laurens, Henri ; Leger, Fernand ; Malevich, Kasimir ; Manessier, Alfred ; Matisse, Henri ; Mondriaan, Piet ; Music, Zoran ; Picasso, Pablo ; Rodin, Auguste ; Rothko, Mark ; Rouault, Georges ; Soulages, Pierre ; Soutine, Chaim ; de Staël, Nicolas ; Tobey, Mark ; Ubac, Raoul ; Vieira da Silva, Maria Elena ; de Vlaminck, Maurice
biografie
Aspects of Twentieth Century Art, Marlborough Fine Art Ltd., London, summer exhibition, July - August 1963
Engels
boek